County Smoke-Free Laws and Asthma Discharges: Evidence from 17 US States - Glenn M. Landers; Patricia Ketsche; Mark L. Diana; Claudia Campbell (Canadian Respiratory Journal)
Background. Although approximately 82 percent of the US population was covered by some form of law that restricted smoking in public establishments as of 2014, most research examining the relationship between smoke-free laws and health has been focused at the state level. Purpose. To examine the effect of county workplace smoke-free laws over and above the effect of other (restaurant or bar) smoke-free laws on adult asthma. Methods. The study estimated the effect of rates of adult asthma discharges before and after the implementation of county nonhospitality workplace smoke-free laws and county restaurant and bar smoke-free laws. Data were from 2002 to 2009, and all analyses were performed in 2011 through 2013. Results. A statistically significant relationship (−5.43, p<.05) was found between county restaurant or bar smoke-free laws and reductions in working age adult asthma discharges. There was no statistically significant effect of nonhospitality workplace smoke-free laws over and above the effect of county restaurant or bar laws. Conclusions. This study suggests that further gains in preventable asthma-related hospitalizations in the US are more likely to be made by focusing on smoke-free laws in bars or restaurants rather than in nonhospitality workplaces.